The Strong Anti-Kinetoplastid Properties of Bee Propolis: Composition and Identification of the Active Agents and Their Biochemical Targets - Godwin U. Ebiloma; Nahandoo Ichoron; Weam Siheri; David G. Watson; John O. Igoli; Harry P. De Koning (Molecules, 2020)
The kinetoplastids are protozoa characterized by the presence of a distinctive organelle, called the kinetoplast, which contains a large amount of DNA (kinetoplast DNA (kDNA)) inside their single mitochondrion. Kinetoplastids of medical and veterinary importance include Trypanosoma spp. (the causative agents of human and animal African Trypanosomiasis and of Chagas disease) and Leishmania spp. (the causative agents of the various forms of leishmaniasis). These neglected diseases affect millions of people across the globe, but drug treatment is hampered by the challenges of toxicity and drug resistance, among others. Propolis (a natural product made by bees) and compounds isolated from it are now being investigated as novel treatments of kinetoplastid infections. The anti-kinetoplastid efficacy of propolis is probably a consequence of its reported activity against kinetoplastid parasites of bees. This article presents a review of the reported anti-kinetoplastid potential of propolis, highlighting its anti-kinetoplastid activity in vitro and in vivo regardless of geographical origin. The mode of action of propolis depends on the organism it is acting on and includes growth inhibition, immunomodulation, macrophage activation, perturbation of the cell membrane architecture, phospholipid disturbances, and mitochondrial targets. This gives ample scope for further investigations toward the rational development of sustainable anti-kinetoplastid drugs.